Implementation of Learning Media with the Concept of "Prop Hunt - QR Coin" to Increase Student Learning Participation in IPS Subjects - Pratama, Bima Wahyu; Kurniawan, Bayu; Wati, Arista; Rahayu, Linda Zulkifa (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This study aims to develop the “Prop Hunt – QR Coin” learning media to enhance student participation in Social Studies (IPS) learning. Employing a Research and Development (R&D) approach with the Design Thinking model, the media integrates gamification and QR Code technology. Conducted in class 8F Tahfidz at SMP Laboratorium Universitas Negeri Malang in 2025, the results showed an increase in student participation from an average score of 40 to 82, with 88% of students meeting the completion criteria. The media effectively motivated students and facilitated interactive learning. Recommendations for future research include expanding implementation to other subjects and incorporating digital literacy training.